The Influence Of Electronic Word Of Mouth On Interest In Saving With Brand Image And Brand Trust As Mediating Variables In Cycle Plus Product Customers In Bank Jatim Surabaya Main Branch - Johanes Koento (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Purpose: This paper aims to analyze the influence of electronic word of mouth against the customer’s interest in saving with brand image and brand trust as mediation in customers who buy the cycle plus product in Bank Jatim Surabaya. Design/methodology/approach: The method used is statistic-descriptive and the design used is cross sectional. Findings: 3 out of 7 hypotheses are rejected while the other 4 is accepted. Research limitations/implications: Variables considered in this study are electronic word of mouth, brand image, brand trust, and interest in saving. The samples are 140 respondents from Bank Jatim Surabaya that were chosen using purposive sampling. Practical implications: Results show that from the 7 hypotheses proposed, only 3 that are rejected. Originality/value: This paper is original. Paper type: This paper can be categorized as a case study. Keyword: brand image; brand trust; electronic word of mouth; saving interest